2020
DOI: 10.1021/acs.nanolett.0c00348
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analyses of the Interfacial Properties of Current Collectors at the Mesoscopic Level in Lithium Ion Batteries by Using Hierarchical Graphene

Abstract: At the mesoscopic level of commercial lithium ion battery (LIB), it is widely believed that the poor contacts between current collector (CC) and electrode materials (EM) lead to weak adhesions and large interfacial electric resistances. However, systematic quantitative analyses of the influence of the interfacial properties of CC are still scarce.Here, we built a model interface between CC and electrode materials by directly growing hierarchical graphene films on commercial Al foil CC, and we performed systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Notably, the signal of COAl bonding detected for Al@G substantiates that graphene is chemically bound to native Al oxide, confirming the strong adhesion and good electrical contact between the in situ‐grown graphene overlayer and the Al foil. [ 22 ] Mechanical peeling‐off tests [ 23 ] (Figure S9, Supporting Information) demonstrated that the average adhesion strength of the modified layer on the Al foil was ≈1.72 and 10.52 N m −1 for Al@C and Al@G, respectively (Figure 1i). After the tests, most of the graphene layer in Al@G was retained, whereas the carbon coating in Al@C was almost completely peeled off (Figure 1i, inset).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the signal of COAl bonding detected for Al@G substantiates that graphene is chemically bound to native Al oxide, confirming the strong adhesion and good electrical contact between the in situ‐grown graphene overlayer and the Al foil. [ 22 ] Mechanical peeling‐off tests [ 23 ] (Figure S9, Supporting Information) demonstrated that the average adhesion strength of the modified layer on the Al foil was ≈1.72 and 10.52 N m −1 for Al@C and Al@G, respectively (Figure 1i). After the tests, most of the graphene layer in Al@G was retained, whereas the carbon coating in Al@C was almost completely peeled off (Figure 1i, inset).…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) analysis presents that the kinetics of lithium ion transport is faster in the LiFePO 4 /GAF battery than in the LiFePO 4 /Al battery (Figures S10 and S11). At least two reasons can account for this: First, the surface of GAF is much rougher than that of Al foil, which makes the contact between GAF and the active material closer. Second, GAF and conductive carbon black have the same work function, while Al foil and conductive carbon black have different work functions in the cell, which allows electrons to pass through the interface between GAF and the active material more smoothly. , …”
Section: Resultsmentioning
confidence: 99%
“…(2) large interfacial electric resistance resulting from the poor contact and weak adhesion between current collectors and electrode materials (Fig. 11(a)), which hampers the rate capability especially for flexible LIBs [133]. With high electrical conductivity, low mass density, and structural tunability, graphene has been widely reported as the free-standing CC or the conductive coating on the traditional CC for LIBs to achieve better wetting, stronger adhesion, greater mechanical durability, and lower contact resistance (Figs.…”
Section: Current Collectormentioning
confidence: 99%
“…Interface design between current collector and electroactive materials plays a key role in the charge transport for lithiumion batteries. Graphene-coated metal foils as current collectors benefit rate capability as the graphene coating could effectively reduce interfacial electric resistance [133,135,[140][141][142]. Recently, Hailin Peng et al proved interfacial electric resistance dominates, i.e., ~ 2 orders of magnitude higher than that of electrode materials, through systematic quantitative studies of the interfacial properties.…”
Section: Coating On Current Collectormentioning
confidence: 99%
See 1 more Smart Citation